EPISTEMOLOGI KARL RAYMOND POPPER DAN KONSTRIBUSINYA PADA STUDI-STUDI KEISLAMAN - Rabiaty, Rahmi (STAI AL FALAH Banjarbaru, 2019)
Popper as one of the figures in Philosophy of Science has offered an idea of the falsification of science. This idea can certainly be used by Islamic studies as long as it can be relevant to the needs faced. Popper's ability to criticize the tendency of verification-mechanistic Positivism can provide added value to Islamic studies, especially given that Islam does not only appreciate the material areas that tend to be mechanistic but also spiritual areas that tend to be of qualitative value. Therefore, the basic question in this paper is how is the construction of Popper's theory of knowledge and its contribution to Islamic studies? The method used in this paper is descriptive-qualitative in that it seeks to describe Popper's knowledge of thought, especially those related to Falsification, and give it meaning for Islamic studies. The results of this paper indicate that Popper's theory of Falsification is 'wrong testing' for a theory because each theory is considered a hypothesis, a transient truth, so that if the theory survives from the 'false test' then the theory will be stronger. As for its relevance to Islamic studies, this enables Islam to accept various variations in the application of universal values promoted by Islam at the level of reality to be open to being tested wrongly so that reality can be found that is close to objective universal values. Keywords: Karl Raymond Popper's Epistemology, Islamic studies